Dynamics of legal regulation of exemptions in the payment and calculation of land fees in the conditions of martial law on the basis of judicial practice - Harkusha, Vladyslav (Problems of legality, 2024)
The relevance of the research topic is stipulated by the new challenges faced by our country in connection with the armed aggression of the Russian Federation against Ukraine and the need to adapt the legal regulation of land payment in terms of its calculation and payment during the period of martial law. The purpose of the article is to trace the dynamics of legal regulation of land payment during martial law, and to review the current case law of both national courts regarding the resolution of disputes on the cancellation of a tax assessment notice and the case law of the European Court of Human Rights in terms of determining the conceptual foundations for the construction of legal provisions. The study of the issue of payment and accrual of land payment is of both applied and theoretical nature, since violation of the means and rules of rule-making technique leads to tax disputes. The analysis of legal constructions of the Tax Code of Ukraine and other regulatory legal acts made it possible to identify problems in the regulation of land payment, which consist in violation of the rule of law principle provided for by the Constitution of Ukraine. The Constitutional Court of Ukraine has defined the principles of legal certainty and legal predictability as components of the rule of law. The inconsistency of the provisions of the Tax Code of Ukraine and bylaws has led to a dual interpretation of their rights and obligations by taxpayers and controlling authorities. The author analyzes the positions of the controlling authorities in terms of amendments to the regulation of the calculation and payment of tax liabilities for taxation of land plots located in the temporarily occupied territories or in the territories where military operations are (were) conducted.